2009
DOI: 10.1074/jbc.m109.021030
|View full text |Cite
|
Sign up to set email alerts
|

Low Density Lipoprotein Receptor-related Protein 1 Promotes Anti-apoptotic Signaling in Neurons by Activating Akt Survival Pathway

Abstract: The low density lipoprotein receptor-related protein 1 (LRP1) is a multi-ligand receptor abundantly expressed in neurons. Previous work has shown that brain LRP1 levels are decreased during aging and in Alzheimer disease. Although mounting evidence has demonstrated a role for LRP1 in the metabolism of apolipoprotein E/lipoprotein and amyloid-␤ peptide, whether LRP1 also plays a direct role in neuronal survival is not clear. Here, we show that LRP1 expression is critical for the survival of primary neurons unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 66 publications
5
94
1
Order By: Relevance
“…This could potentially result in the formation of RBD-A␤ complexes (24) that accelerate ␤-amyloid-mediated neuronal degeneration (54). Yet other reports indicate that LRP1 agonists might reduce aberrant amyloid precursor protein processing (55) and that LRP1-dependent cell signaling in neurons and glia appears to consistently result in prosurvival effects (56). Moreover, the LRP1 ligand derived from the hemopexin domain of matrix metalloproteinase 9, PEX, does not bind A␤ and would be unlikely to influence Alzheimer's disease-related pathology.…”
Section: Discussionmentioning
confidence: 99%
“…This could potentially result in the formation of RBD-A␤ complexes (24) that accelerate ␤-amyloid-mediated neuronal degeneration (54). Yet other reports indicate that LRP1 agonists might reduce aberrant amyloid precursor protein processing (55) and that LRP1-dependent cell signaling in neurons and glia appears to consistently result in prosurvival effects (56). Moreover, the LRP1 ligand derived from the hemopexin domain of matrix metalloproteinase 9, PEX, does not bind A␤ and would be unlikely to influence Alzheimer's disease-related pathology.…”
Section: Discussionmentioning
confidence: 99%
“…In the neurons of dendritic synapses, LRP1 interacts with the N-methyl-D-aspartate receptor to modulate neuronal calcium signaling (15). Neuronal expression of LRP1 also activates protein kinase B/Akt signaling in protection against stress-induced apoptosis (16). In addition, LRP1 has been shown to participate in focal adhesion and cell migration via direct association with integrins and/or modulation of calreticulin/thrombospondin signaling events (17,18).…”
Section: Hepatocytes Finally Hlrp1mentioning
confidence: 99%
“…98,99) A deficiency of LRP1 in neurons induces activation of caspase 3, a decrease of Akt phosphorylation and a decrease in the level of the insulin receptor, as well as the progression of apoptosis. 100) Binding of ligands, such as tissue-type plasminogen activator or a2-macroglobulin, to LRP1 in neurons transactivates the Trk receptor by activation of Src family kinase, suggesting that these ligands may have neurotrophic activity. 101) We have also reported that another ligand for LRP1, apo E associated with lipid, induces a strong anti-apoptotic effect and protects against neurodegeneration through an intracellular signaling pathway.…”
Section: Ldl Receptor Family Members In the Cnsmentioning
confidence: 99%